Laryngotracheal Abnormalities in Esophageal Atresia Patients: A Hidden Entity - Conforti, Andrea; Valfrè, Laura; Scuglia, Marianna; Trozzi, Marilena; Meucci, Duino; Sgrò, Stefania; Bottero, Sergio; Bagolan, Pietro (Frontiers in Pediatrics, 2018)
Importance: Presence of laryngotracheal abnormalities is associated with increased morbidity and higher mortality rate in esophageal atresia patients. Objective: Determine the prevalence of laryngotracheal abnormalities (LTA) in a prospectively collected cohort of patients treated for esophageal atresia and/or tracheoesophageal fistula (EA/TEF). Analysis of the impact of those airway anomalies in early postoperative outcomes was performed. Patients and Methods: This was a prospective case series study, including patients from January 2008 to December 2017. Patients enrolled in the present study were treated in a high-volume referral center. Present study included all newborn-infants consecutively treated for EA/TEF. All patients were evaluated by flexible laryngotracheoscopy performed under local anesthesia in spontaneous breathing. In case of airway malformation suspected during flexible endoscopy, a rigid endoscopy was performed to complete airway assessment. If post-operative respiratory symptoms (noisy breathing, respiratory difficulty, failure to extubate, or difficulty feeding) were noted, a second laryngotracheoscopy was performed. Primary study outcome was to evaluate the prevalence of LTA in EA/TEF infants, characterizing of LTA, and their impact on early postoperative outcomes. Those primary study outcomes were planned before data collection began. Results: During the study period 207 patients with EA/TEF were treated. LTA had a period prevalence of 40.1% (83/207). Although no differences were recorded in terms of demographics and clinical presentation, LTA+ infants more frequently required tracheostomy (12/52, 23% vs. 0/124, 0%; p 0.0001) and were at increased risk of death (12/83, 14% vs. 5/124, 4%; p0.009) in comparison with EA/TEF without LTA. Conclusions: Present data suggest a high prevalence of congenital LTA in patients affected by EA. Most of the abnormalities are congenital and a high proportion of patients with LTA require a tracheostomy. Mortality significantly correlates with the presence of LTA. Systematic airway endoscopic preoperative evaluation has to be pushed forward to minimize LTA-related morbidity and mortality.